Analysis of the factors influencing liver regeneration after hepatectomy in hepatocellular carcinoma patients and the relationship between liver regeneration and prognosis - Hongliang Liu; Xiaojing Gai; Xi Wang; Lingyan Liu; Lantian Tian; Bin Zhou (Scientific Reports)
Abstract We sought to investigate the factors influencing liver regeneration after hepatectomy for hepatocellular carcinoma and the relationship between liver regeneration and prognosis. This retrospective cohort study enrolled 92 hepatocellular carcinoma (HCC) patients undergoing hemihepatectomy at Qingdao University Affiliated Hospital (2014-2020) with complete CT imaging (postoperative day 3 and month 1) and clinical records. Using Hisense CAS software, we performed three-dimensional liver reconstruction to quantify standardized residual liver volume (SRLV) and calculate hepatic regeneration rate (HRR) at 1-month postoperation. Patients were stratified into high and low-regeneration groups based on median HRR. Univariate analysis and multivariate logistic regression were applied to identify factors influencing regeneration. Kaplan-Meier survival curves with log-rank tests analyzed tumor-free survival (TFS) and overall survival (OS) outcomes in relation to regeneration capacity. The cohort comprised 61 right and 31 left hemihepatectomies. Median 1-month HRR was 17.6% overall, with significant disparity between right (20.29%) and left hepatectomy subgroups (12.2%). Univariate analysis identified age, sex, alcohol history, hepatitis B status, cirrhosis severity, and SRLV as significant regeneration predictors (all P < 0.05). Multivariate modeling established cirrhosis severity (OR = 0.217, 95% CI:0.064–0.732, P = 0.014) and SRLV (OR = 0.989, 95% CI:0.982–0.995, P < 0.001) as independent determinants.Prognostically, high-regeneration patients exhibited extended median TFS (16 vs. 5 months, P<0.05) compared to low-regeneration counterparts, though no significant OS difference was observed (P>0.05). Cirrhosis severity and standardized residual liver volume (SRLV) independently predict post-hemihepatectomy liver regeneration in HCC patients. Preoperative 3D reconstruction-guided SRLV assessment combined with cirrhosis evaluation optimizes surgical planning. Enhanced hepatic regeneration correlates with shorter tumor-free survival (median 16 vs 5 months, P＜0.05), necessitating intensified surveillance in high-regeneration cohorts to mitigate recurrence risks.